Enriching and Managing Islamic Digital Resources: The Need for Special Skills and Competencies for the Ummah - Shahar Banun Jaafar (Universiti Sains Islam Malaysia, 2024)
During the Islamic Golden Age, sometimes known as Islamic Renaissance, which dated from the 8th Century to the 16th Century, Muslim scholars had contributed in science, mathematics, astronomy, philosophy, medicine, arts, literature and many others. Arts flourished, including metal work, textiles (especially silk), the making of illuminated Qur'ans, and calligraphy. Many invention and innovation were made which became the basis of today’s knowledge. From the time of the Prophet Muhammad SAW (pbuh) to the time of the Umayyad Caliphate, Abbasid Caliphate, Faṭimid Caliphate, Ottomans Empire, Islam spread from the Arab Continent to Africa, Central Eastern Europe, Central Asia, China and to Southeast Asia, creating the Islamic civilization which kept the knowledge alive and passed it to others. Al-Quran and the Prophet Muhammad (pbuh) urged all Muslims to teach themselves and seek knowledge. The Prophet Mohammed (pbuh) taught Muslim in Darul Arqam, the first school for early Muslims in Mecca. When the Prophet (pbuh) went to Madinah and built mosques, education became one of the most important functions of the mosque. Knowledge became the basis for cultural, educational and economic development at the time.1 In the 9th to 10th Century many learning centers – madarasah-colleges, mosque-universities - were established in the Muslim world. Harun al-Rashid opened the School – Baytul Hikmah also known as “The house of Wisdom” – in Baghdad where Islamic studies, Arabic language, literature, mathematics and history were taught and many books were translated to Arabic languages, the language of education of that time. There were a Department of Library and Translation in Baytul Hikmah. Knowledge was institutionalized and proliferated during the golden time. Other learning centers such as Al-Qarawiyyin in Fez, the Al- Zaytuniah in Tunisia and Al Azhar in Cairo were renounced for producing prominent Islamic scholars. The Al-Madarasah Nazamiyya which was established by the Suljuk ruler al-Arsalam in 1063 CE spread to Baghdad, Alexandria in Egypt, Damascus, Samarkhand, Bokhara, and many other Islamic cities. The organization of Al-madarasah Nazarmiyya were said to be copied by the early universities in Europe.2 Muslim began manufacturing papers, learning from the Chinese when Islam spread to China. The ample supply of papers activated Muslim scholars, calligraphers and copyists to write and reproduce books. Educational cultural centers known as Suq-al-Warriqin were established as a place for copying, reproducing as well as places where scholars met and discussed about different branches of knowledge. Many Islamic scientific and philosophical texts were translated into several languages including Latin and gradually become available to the philosophers of the West.